Extraction, Fractionation, Phytochemical Profile, Antioxidant, and Antimicrobial Activities of Cassia absus L. and Citrus medica L. - Zartasha Kousar; Surryia Manzoor; Saima Naz; Muhammad Shafiq Shahid (Pharmaceutical and Biomedical Research, 2023)
Background: Cassia absus L. and Citrus medica L. plants are sources of different phytochemicals with pharmaceutical significance. They are biochemically distinctive and used in producing various herbal products with exclusive bioactivity. Also, the extraction of these phytonutrients with medicinal characteristics has recently increased. Objectives: We determined to evaluate the plant-derived compounds such as polyphenols and antioxidant and antimicrobial activity of the methanolic extract of Cassia absus L. and Citrus medica L. Methods: Antioxidant activity was calculated through linoleic acid inhibition, determination of reducing power, and 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging assay. The disk diffusion method was used for assessing antimicrobial activity. Various solvents such as acetic acid, ethanol, acetone, n-hexane, and ethyl acetate were used to perform partition fractionation of the methanolic extract of plants. Results: Three major components were analyzed through high-performance liquid chromatography in C. absus and C. medica. Total phenolic contents varied from 5.58-17.1 to 2.66-7.41 per 100 g examined through Folin-Ciocalteu reagent, pointed as gallic acid equivalents (GAE), and total flavonoid contents lined from 11.50-32.4 to 24.91-36.36 per 100 g specified as catechin equivalents. Inhibition rate and reducing potential were greater in C. medica fractions of 49.6% and 1.14, respectively. The C. medica solvent fractions exhibited greater radical scavenging activity in the DPPH assay at 80%. C. absus and C. medica extract significantly inhibit different gram-negative (Escherichia coli, Pasteurella multocida, and Fusarium) and gram-positive bacteria (Staphylococcus aureus, Bacillus subtilis, Aspergillus flavus, Aspergillus niger, and Fusarium Solani) bacteria. Conclusion: Both leaf extracts of C. absus and C. medica could have potential applications in agriculture, pharmaceutics, and medicine.